DMSO as a dual carbon synthon in one-pot tandem synthesis of N-alkylated quinazolinones from anthranilamides and acetophenones. (8th August 2022) - Yadav, Pushpendra; Yadav, Sourabh; Awasthi, Annapurna; Phanindrudu, Mandalparthi; Bhowmick, Suman; Tiwari, Dharmendra Kumar
Abstract : DMSO-assisted approach for the synthesis of N -alkylated quinazolinones from readily available 2-aminobenzamide and aryl methyl ketones has been developed. DMSO played a dual role, acting as a solvent as well as a dual carbon synthon, making this process an environmentally benign approach. Abstract : A new, efficient, metal-free, and DMSO-assisted approach for the synthesis of N -alkylated quinazolinones from readily available 2-aminobenzamide and aryl methyl ketones in the presence of an oxidizing agent has been developed. In this unique tandem reaction, DMSO played a dual role, acting as a solvent as well as a dual carbon synthon, making this process an environmentally benign approach to accessing medicinally prevalent N -alkylated quinazolinones. The DMSO-assisted in situ generation of an iminium cation and α, β-unsaturated ketones from 2-aminobenzamide and aryl methyl ketones, respectively, is the key feature involved in this method.